Correction: Corrigendum: Geographic population structure analysis of worldwide human populations infers their biogeographical origins - Eran Elhaik (Nature Portfolio, 2016)
Nature Communications 5: Article number: 3513 (2014); Published: 29 April 2016; Updated: 31 October 2016 This article was published without any competing financial interests statement. A revised declaration that lists potentially competing financial interests is provided below: A.D.M., M.M. and M.A.are affiliated with Bcs Biotech S.